Time-migrated multichannel seismic data and separated diffraction energy, sediment echosounder data and calculated grids from the Langeland Fault System, Baltic Sea - Ahlrichs, Niklas; Hübscher, Christian; Andersen, Theis Raaschou; Preine, Jonas; Bogner, Laura; Schäfer, Wiebke (PANGAEA, 2023)
The understanding of the dynamics and scales of glacially induced faulting greatly benefits from an analyis using multiple geophysical datasets. By using a combination of high-resolution 2D seismic reflection data in combination with diffraction imaging, sediment echosounder data and shallow wells, we investigate a fault and graben system offshore Langeland Island in the Baltic Sea, which we term the Langeland Fault System. This approach allows to unravel the spatial character of the Langeland Fault System along an elevated basement block of the Ringkoebing-Fyn High. Our analysis shows the continuation of deep-rooted faults up to the seafloor. Imaging the shallowmost strata reveals Quaternary fault reactivation during glacial or postglacial times. This combination of imaging techniques is rarley realized in the onshore hinterland, thus, representing a unique analysis of Quaternary fault reactivation by combining onshore and offshore data and methods. Seismic data was acquired in September 2020 during a student field exercise cruise onboard R/V Alkor. The survey was organized by the University of Hamburg (Cruise AL545). Seismic data acquisition was carried out using a Mini-GI gun (true GI-mode with a 15 in³ generator and 30 in³ injector volume) and a 48-channel streamer with 4 m group spacing. The data have a dominant frequency of 250 Hz. Signal penetration is up to 1 s two-way travel time (TWT). The seismic processing routine included frequency filtering, amplitude recovery, noise reduction, surface-related multiple attenuation (SRME), Kirchhoff time migration. Innomars SES 2000 parametric sub-bottom profiler, which is hull-mounted on R/V Alkor, was used for the acquistion of the sediment echosounder data (Primary frequencies of about 100 kHz, secondary parametric frequency: 8 kHz). The diffraction imaging is based on separating the dominant reflected wavefield through a coherent summation scheme guided by a dip-based wavefront filter. In a next step, the reflection-only data is subtracted from the input data. The diffraction-only data is then focused using FD migration. By calculating the squared envelope of the focused diffractions, the diffraction energy stacks are obtained. The mapping procedure includes gridding using all available profiles in order to create time-structure maps by minimum curvature spline interpolation. Isochron maps (vertical thickness in two-way time) for the Triassic to Quaternary units were calculated by subtracting the top and bottom horizons of the specific units.
Keywords: Baltic Sea; Diffraction imaging; Glacially induced faults; Langeland; reflection seismics; sediment echosounder; Seismic; thickness maps; time-structure maps